About the Coupling Factor Influence on the Ground Fault Current Distribution on Overhead Transmission Lines - VINTAN, M. (Advances in Electrical and Computer Engineering, 2010)
A phase-to-ground fault occurring on a transmission line divides the line into two sections, each extending from the fault towards one end of the line. These two sections of the line may be considered infinite if some certain conditions are met; otherwise, they must be regarded as finite. This paper treats the case when those two sections of the line are both very long and allows the determination of the ground fault current distribution in power networks. The influence of the coupling factor between the faulted phase and the ground wire on the ground fault current distribution is studied.